2015
DOI: 10.1007/s10895-015-1630-1
|View full text |Cite
|
Sign up to set email alerts
|

Permethylated-β-Cyclodextrin Capped CdTe Quantum Dot and its Sensitive Fluorescence Analysis of Malachite Green

Abstract: In the present work, the CdTe quantum dots were covalently conjugated with permethylated-β-cyclodextrin (OMe-β-CD) using 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride as cross-linking reagent. The obtained functional quantum dots (OMe-β-CD/QDs) showed highly luminescent, water solubility and photostability as well as good inclusion ability to malachite green. A sensitive fluorescence method was developed for the analysis of malachite green in different samples. The good linearity was 2.0 × 10(-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 30 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Researchers have found that water-soluble QDs could be used as selective inorganic ion probes to determining CN À , H + , Ag + , Hg 2+ , Cu 2+ , Fe 2+ , Ni 2+ , Pb 2+ , Mn 2+ , Zn 2+ , and Co 2+ (22)(23)(24)(25)(26)(27). Interestingly, cationic dyes and surfactants can quench QDs extensively (28,29). Quenching results from variations in QD surface structures.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that water-soluble QDs could be used as selective inorganic ion probes to determining CN À , H + , Ag + , Hg 2+ , Cu 2+ , Fe 2+ , Ni 2+ , Pb 2+ , Mn 2+ , Zn 2+ , and Co 2+ (22)(23)(24)(25)(26)(27). Interestingly, cationic dyes and surfactants can quench QDs extensively (28,29). Quenching results from variations in QD surface structures.…”
Section: Introductionmentioning
confidence: 99%